Role for circadian clock genes in seasonal timing: testing the bünning hypothesis. - Pegoraro, M.; Gesto, J.S.; Kyriacou, C.P.; Tauber, E. (PLoS Genetics, 2014)
A major question in chronobiology focuses around the "Bünning hypothesis" which implicates the circadian clock in photoperiodic (day-length) measurement and is supported in some systems (e.g. plants) but disputed in others. Here, we used the seasonally-regulated thermotolerance of Drosophila melanogaster to test the role of various clock genes in day-length measurement. In Drosophila, freezing temperatures induce reversible chill coma, a narcosis-like state. We have corroborated previous observations that wild-type flies developing under short photoperiods (winter-like) exhibit significantly shorter chill-coma recovery times (CCRt) than flies that were raised under long (summer-like) photoperiods. Here, we show that arrhythmic mutant strains, per01, tim01 and ClkJrk, as well as variants that speed up or slow down the circadian period, disrupt the photoperiodic component of CCRt. Our results support an underlying circadian function mediating seasonal daylength measurement and indicate that clock genes are tightly involved in photo- and thermo-periodic measurements.